As desigualdades intra-regionais e suas interrelações no processo de desenvolvimento da educação escolar: o caso matogrossense - Moreno, Gislaene (1982)
We examine here the problem of economic and social inequalities in the State of Mato Grosso and their relationship with shooling in terms of access, promotion, and formal equality. By means of a very simple quantitative and qualitative methodology, we start from the assimplion that schooling tends to be positively related to the existing disparities in a given area or region. The analysis of economic social and education all indicators lead us to confirm such an idea. It demonstrated that the poorer a region or county is, the poorer or more deficient is the formal equality of schooling. In this sense, though it may function as an instrument for I1conscientizationll, in the very it has been implemented it only can serve for keeping the current inequalities.